2018
DOI: 10.1177/2325967118s00078
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Medial Patellofemoral Ligament Reconstruction for Patellar Instability Regardless of the Tibial Tubercle Trochlear Groove Distance: Outcomes at 1 and 2 Years

Abstract: Background:Several surgical options exist for treatment of recurrent patellar instability. The treatments can be divided into ligamentous and bony procedures. It is currently unclear which patients require a bony procedure in addition to a soft tissue reconstruction.Purpose:To report the one and two-year outcomes of patients following medial patellofemoral ligament (MPFL) reconstruction performed in isolation regardless of the patellar height, tibial tubercle trochlear groove distance (TT-TG) or trochlear dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the treatment algorithm for lateral patellar instability, medialization of the tibial tubercle is recommended in cases of TT-TG distance 20 mm. Erickson et al 7 recently reported encouraging results with isolated MPFL reconstruction irrespective of TT-TG distance. This is in accordance with our study, and we believe that this approach is made possible by the use of a hamstring autograft, which provides a much stiffer and stronger structure than the native MPFL.…”
Section: Discussionmentioning
confidence: 96%
“…In the treatment algorithm for lateral patellar instability, medialization of the tibial tubercle is recommended in cases of TT-TG distance 20 mm. Erickson et al 7 recently reported encouraging results with isolated MPFL reconstruction irrespective of TT-TG distance. This is in accordance with our study, and we believe that this approach is made possible by the use of a hamstring autograft, which provides a much stiffer and stronger structure than the native MPFL.…”
Section: Discussionmentioning
confidence: 96%